The Effect Of Intensive Keramba On The Presence Of Parasite Organisms In Rivers Of Lingsar Area - Supriadi Supriadi; Maratun Janah (Biology, Medicine, & Natural Product Chemistry, 2015)
The application of intensive keramba in rivers could affect the presence of parasite organisms throughout  the river downstream. The aims of this research are to find out the diversity of parasite species and the effect of intensive aquaculture method developed by the community on the presence of various parasitic organisms, particularly in the downstream area. A total of 65 Tilapia fish samples (O. niloticus) that was collected from 3 areas ( 15 samples from upstream, 25 samples in keramba and 25 samples from downstream areas) have been examined  in the laboratory of Faculty of Mathematic and Natural Science, University of Mataram. Methods employed  to identify parasites that  infected fish samples are native method and flotation method. This research has identified 7 species of parasites which were divided into 2 groups: ectoparasites (Trichodina sp., Amylodinium sp., Oogonium sp., Dactylogirus sp., Trematode) and endoparasites (Entamoeba sp. dan Camallanus sp.). Diversity index calculation  indicated that parasite organisms in upstream area were lower in number than that in the downstream and intensive karamba area (H’= (0,825; 1,596 dan 1.324 respectively).  These data has showed there was a difference in species diversity and evenness index of parasite organisms in the upstream, downstream and intensive keramba area. In conclusion, there was significant influence of the application of intensive keramba on the appearance of various parasite organisms that could affect the sustainability of  fish aquaculture.